Intervening to Prevent Repeat Offending Among Moderate- to High-Risk Domestic Violence Offenders: A Second-Responder Program for Men. (March 2015) - Scott, Katreena; Heslop, Lisa; Kelly, Tim; Wiggins, Kate
Clear directions about best strategies to reduce recidivism among domestic violence offenders have remained elusive. The current study offers an initial evaluation of an RNR (Risk, Needs, and Responsivity)-focused second-responder program for men accused of assaulting their intimate partners and who were judged as being at moderate to high risk for re-offending. A quasi-experimental design was used to compare police outcomes for 40 men attending a second-responder intervention program to 40 men with equivalent levels of risk for re-offense who did not attend intervention (comparison group). Results showed that there were significant, substantial, and lasting differences across groups in all outcome domains. In terms of recidivism, rates of subsequent domestic-violence-related changes were more than double for men in the comparison group as compared with the intervention group in both 1-year (65.9% vs. 29.3%) and 2-year (41.5% vs. 12.2%) follow-up. Changes in the rates of arrest were consistent with reductions in men's general involvement with police, with men in the intervention group receiving fewer charges for violent offenses, administrative offenses, and property offenses over the 2 years following intervention than men in the comparison group. Not surprisingly, these differences result in a much lower estimated amount of police time with intervention men than for comparison men. Results are discussed with reference to the possible impact of sharing information with men about their assessed risk for re-offending within a therapeutic justice context.